Utilização do ORC( Western Ontário Rotator Cuff Index) e ultrassonografia do ombro para avaliação de qualidade de vida de pacientes submetidos à osteossìntese do úmero com haste intramedular bloqueada com acesso anterógrado - Cocco, Luiz Fernando [UNIFESP] (2018)
Background: This study evaluates the quality of life through the WORC Protocol (Western Ontario Rotator Cuff Index --- Validated for Brazil) for 5 different domains (Physical Symptoms, Sports / Recreation, Work, Lifestyle, Emotions) from patients submitted to humeral fractures fixation with antegrade locked intramedullary nailing. The study demonstrates the consequences after the implantation of the rotator cuff transfixation and helps in decision making for treatments of these fractures. Methods: Search and Call of patients (N=26) were submitted to Humerus Osteosynthesis with Antegrade Locked Intramedullary Nailing for evaluation of the quality of life through the WORC Protocol. Mann---Whitney test was used to evaluate the association between numerical variables (age, last surgery and quality of life scores) and the Chi---Square and Fisher tests for the categorical variables (sex, laterality, dominance, work leave). We used p <0.05 for significance. Results: The overall WORC score was 82.75 ± 17.00 (Mean + SD) and was not different considering sex, age and postoperative period. Among the WORC domains, both Work and Sport / Recreation Protocols were the most unfavorable factors in the evaluation of patients, with a mean of 10.54 ± 9.00 and 7.36 ± 8.44, respectively. Although not statistically significant, those who had the procedure on the dominant side presented a lower quality of life score (78.1 ±18.9) than those who had surgery on the non---dominant side (86.7 ± 13.9, p = 0.20). Although non significant again, those who were away from work had an overall lower quality of life score (69.2 ± 21.1) than those who were not (85.9 ± 14.2, p = 0.10). Conclusions: Intramedullary nailing with antegrade access can be used to treat fractures of thehumerus without compromising the quality of life of patients. Although it is a safe implant option, considerations for its indication regarding work return and sports or recreational practices should be considered.